Implementasi Penilaian Kesehatan Bank Syariah Indonesia (BSI) Berdasarkan Peraturan Otoritas Jasa Keuangan (POJK) 2/POJK.03/2022 - Iswanto, Yuni; Mulyani, Hendarti Tri Setyo (Budgeting: Jurnal Akuntansi Syariah, 2024)
An assessment regarding the health of Banks in Sharia Banking is also carried out, both the health of Sharia Banks and Sharia Rural Banks are assessed. As time progresses, the method of assessing the condition of a bank will have a dynamic nature which is expected to encourage re-regulation of a system used to assess the level of bank health based on sharia principles. Regulations used by the Financial Services Authority or abbreviated as (POJK) No. 8/POJK.03/2014 concerning the soundness level of all sharia-type commercial banks and all sharia business units which were created in an effort to increase the effectiveness of assessing the level of bank health in an effort to face several changes that involve business complexity and various risk profiles. from a bank or subsidiary company of the bank itself. This research will use an appropriate method for conducting assessments, namely CAMELS to assess the syari’ah Bank’s Healh. This research will use a qualitative approach. The research approach using a qualitative method is a method that will be based on post-positivism type philosophy which will later be used to be able to research in very natural or natural conditions where the researcher will be a key instrument in this research. The assessment period is carried out at least every 1 semester (6 months) and data must be updated if necessary at any time. There are several factors that become assessments that measure the level of bank health which can later be used in a sharia type commercial bank.